Decision Support System for Achieving Scholarship Selection by Using Profile Matching Method - Handayani, Rani Irma; Triningsih, Triningsih; Putri, Melia (Politeknik Ganesha Medan, 2020)
Learning is one of the obligations of students to do in every school activity where they study. However, sometimes many students are less able to digest the subject matter delivered by the teacher. Therefore, the school held a scholarship program for outstanding students. In order to motivate students to study harder. Achievement scholarships are given with the aim of motivating students to study harder. Currently the scholarship is not right on target because it is still done manually and it is not clear the criteria for a student to get an achievement scholarship. To conduct an assessment in awarding scholarships to high achieving students use a decision support system to help solve a problem. For this reason, to conduct an assessment in the awarding of scholarships, a decision support system using the Profile Matching method is used. Profile Matching method is one of the methods used in decision making. In this study, there are several aspects of the assessment for awarding achievement scholarships, namely the KKM Aspect, the Attendance Aspect, the Behavior Aspect, the Craft Aspect or the Discipline, the Neatness Aspect.